Glycocalix[4]arenes and their affinity to a library of galectins: the linker matters - Konvalinková, Dorota; Dolníček, František; Hovorková, Michaela; Červený, Jakub; Kundrát, Ondřej; Pelantová, Helena; Petrásková, Lucie; Cvačka, Josef; Faizulina, Margarita; Varghese, Beena; Kovaříček, Petr; Křen, Vladimír; et al. (Organic & biomolecular chemistry, 2023)
Galectins are lectins that bind β-galactosides. They are involved in important extra- and intracellular biological processes such as apoptosis, and regulation of the immune system or the cell cycle. High-affinity ligands of galectins may introduce new therapeutic approaches or become new tools for biomedical research. One way of increasing the low affinity of β-galactoside ligands to galectins is their multivalent presentation, e.g., using calixarenes. We report on the synthesis of glycocalix[4]arenes in cone, partial cone, 1,2-alternate, and 1,3-alternate conformations carrying a lactosyl ligand on three different linkers. The affinity of the prepared compounds to a library of human galectins was determined using competitive ELISA assay and biolayer interferometry. Structure-affinity relationships regarding the influence of the linker and the core structure were formulated. Substantial differences were found between various linker lengths and the position of the triazole unit. The formation of supramolecular clusters was detected by atomic force microscopy. The present work gives a systematic insight into prospective galectin ligands based on the calix[4]arene core.
Keywords: Ligands; galektiny; molekulární konformace; lidé; Galectins; prospektivní studie; glykokalyx; Prospective Studies; Glycocalyx; ligandy; Molecular Conformation; Humans